The Influence of Tea Tree Oil on Antifungal Activity and Pharmaceutical Characteristics of Pluronic® F-127 Gel Formulations with Ketoconazole - Magdalena Wróblewska (MDPI AG, 2021)
Fungal skin infections are currently a major clinical problem due to their increased occurrence and drug resistance. The treatment of fungal skin infections is based on monotherapy or polytherapy using the synergy of the therapeutic substances. Tea tree oil (TTO) may be a valuable addition to the traditional antifungal drugs due to its antifungal and anti-inflammatory activity. Ketoconazole (KTZ) is an imidazole antifungal agent commonly used as a treatment for dermatological fungal infections. The use of hydrogels and organogel-based formulations has been increasing for the past few years, due to the easy method of preparation and long-term stability of the product. Therefore, the purpose of this study was to design and characterize different types of Pluronic® F-127 gel formulations containing KTZ and TTO as local delivery systems that can be applied in cases of skin fungal infections. The influence of TTO addition on the textural, rheological, and bioadhesive properties of the designed formulations was examined. Moreover, the in vitro release of KTZ, its permeation through artificial skin, and antifungal activity by the agar diffusion method were performed. It was found that obtained gel formulations were non-Newtonian systems, showing a shear-thinning behaviour and thixotropic properties with adequate textural features such as hardness, compressibility, and adhesiveness. Furthermore, the designed preparations with TTO were characterized by beneficial bioadhesive properties. The presence of TTO improved the penetration and retention of KTZ through the artificial skin membrane and this effect was particularly visible in hydrogel formulation. The developed gels containing TTO can be considered as favourable formulations in terms of drug release and antifungal activity.